Availability and Utilization of Automated External Defibrillators in New York State Schools - Arabadjian, Milla; Serrato, Stephanie; Sherrid, Mark V. (Frontiers in Pediatrics, 2021)
Background: Use of automated external defibrillators (AEDs) in out-of-hospital cardiac arrests (OHCAs) improve survival. Professional health organizations recommend that AEDs be available in crowded places, including schools but currently only 18 US states require them. Sudden cardiac arrest (SCA) research in the school population has largely focused on school sub-groups, leaving out the majority of US students and adults working in schools. New York State (NYS) has one of the largest student populations in the US. Our objective was to gain epidemiologic data on SCA across a variety of school levels and examine the availability and utilization of AEDs in a state that requires them. Methods: This was an observational, cross-sectional study utilizing an electronic survey. We included NYS school nurses and collected electronic surveys in January-March, 2018. We analyzed demographic data of school characteristics, SCA occurrences and AED use and availability. Results: Of 876 respondents (36.1% response rate), 71 (8.2%) reported SCAs, with 41 occurring in adults. AEDs were deployed in 59 of 71 (84.3%) events, 40 individuals had long-term survival. Most SCAs occurred in middle-schools. School size or number of AEDs/school had no bearing on short-term or long-term survival. AEDs were widely available in private schools, though this was not required by state law. Conclusions: Our data suggest a need for more comprehensive examination of SCA in US schools. Research comparing the availability and utilization of school AEDs between states that do and do not require them is needed and may have important clinical and policy implications for SCA emergency preparedness in US schools.